Recurrent Prolonged Epileptic Fugue State Misdiagnosed as Psychosis? Tale of a Middle-Aged Female Nigerian African - Olowoyo, Paul; Oguntoye, Oluwafunmilayo; Akinbote, John; Mayowa Owolabi, Rufus Akinyemi, (International Journal of Innovative Research in Medical Science, 2018)
A fugue is a state of reversible amnesia for personal identity in which case an individual wanders away from home or place of work for periods of hours, days or even weeks. It could be psychogenic (dissociative) or organic. We report a case of epileptic fugue state in a middle-aged woman treated with carbamazepine after several years of misdiagnosis as a psychotic disorder.